Development of METAGERTA Media based on Smart Apps Creator to Improve Metamorphosis Learning Outcomes in Elementary School - Amanda Dwi Setyo Rani; Deasylina da Ary (CV. Creative Tugu Pena, 2026)
In science learning, especially metamorphosis material at Wonolopo 02 Elementary School, the use of interactive learning media has not been optimally implemented and its development is still limited, so that students experience difficulties in understanding the concepts being studied. This study aims to develop METAGERTA (Metamorphosis through Dance Movement) media based on Smart Apps Creator and to determine its feasibility and effectiveness in improving student learning outcomes on metamorphosis material in elementary schools. This study uses the Research and Development (R&D) method with the ADDIE development model. The research subjects consisted of 28 third-grade students. Data collection techniques were carried out through observation, interviews, questionnaires, and student learning outcome tests. Data were analyzed using quantitative and qualitative approaches. The results of the study show that the development of METAGERTA media based on Smart Apps Creator is equipped with navigation buttons and motion activities, which invite students to learn metamorphosis through motion exploration. METAGERTA media obtained a very feasible category with a value of 94.7% from media experts and material experts. The results of the t-test showed a significant difference between the pretest and posttest scores with a significance of 0.000. In addition, METAGERTA media obtained an N-Gain value on a small scale of 72.1% and a large scale of 71.4%, indicating an increase in student learning outcomes in the high category. Thus, METAGERTA media based on Smart Apps Creator is feasible and effective for use as a learning medium for metamorphosis material in elementary schools.